Autoria, estilo e criatividade: um contraste entre os cursos de escrita criativa e o Wattpad - Moraes, Bianca Barbara Rapelli de (Universidade Federal de São Carlos, 2020)
The creative writing courses are becoming an important support for new authors because of their varied advice on plot, dialogues and other essential elements for a “good story”. Trying to discover how helpful these courses really are, we are going to analyze their lessons and, after, compare them with the concepts of style, authorship and creativity written by Mikhail Bakhtin. Not only that, we will also see how this theory is seen in practice based on some books we found in the digital platform Wattpad, where authors can share their stories for free.
Authorship, style and creativity: a contrast between creative writing courses and Wattpad
Keywords: Autoria; Bakhtin; Criatividade; Escrita; Estilo; Wattpad; Authorship; Creative writing; Style; LINGUISTICA, LETRAS E ARTES::LINGUISTICA